1993
DOI: 10.1002/cber.19931260612
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X‐Ray Structure and Complexation Behavior of the New Tripodal Phosphane Ligand cis, cis‐1,3,5‐Tris[(diphenylphosphanyl)methyl]1‐1,3,5‐trimethylcyclohexane (tdppmtmcy). Crystal Structure of Ir(tdppmtmcy)(CO)Cl

Abstract: The introduction of three methyl groups into the ipso positions of the cyclohexane ring in cis,cis‐1,3,5‐tris[diphenylphosphanyl)methyl]cyclohexane (tdppmcy) (1) leads to the new tripodal phosphane ligand cis,cis‐1,3,5‐tris(diphenylphosphanyl)methyl]1‐1,3,5‐trimethylcyclohexane (tdppmtmcy) (5). The dynamic behavior is studied by variable‐temperature NMR spectroscopy and compared with the structure (X‐ray analysis) in the solid state. Treatment of 5 with Ir(PPh3)2(CO)Cl gives 6 where the two PPh3 groups are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…31 To conrm that the major set of 1 H NMR spectral signals are correctly attributed to the ionic species [ LH Ir][Cl] that was observed in the solid state, the related ionic compound [ LH Ir] [PF 6 ] was synthesized. As hexauorophosphate is a weakly coordinating anion, 32 34 In the 15 examples where H and X are trans to each other, [35][36][37][38][39][40][41][42][43][44][45] the d Ir-H (t) is observed between À15 to À20 with 2 J H-P < 15 Hz. For the 6 complexes with H and CO trans to each other, d Ir-H (t) is reported between À5 and À10, and 2 J H-P between 14-18 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…31 To conrm that the major set of 1 H NMR spectral signals are correctly attributed to the ionic species [ LH Ir][Cl] that was observed in the solid state, the related ionic compound [ LH Ir] [PF 6 ] was synthesized. As hexauorophosphate is a weakly coordinating anion, 32 34 In the 15 examples where H and X are trans to each other, [35][36][37][38][39][40][41][42][43][44][45] the d Ir-H (t) is observed between À15 to À20 with 2 J H-P < 15 Hz. For the 6 complexes with H and CO trans to each other, d Ir-H (t) is reported between À5 and À10, and 2 J H-P between 14-18 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…A trisubstituted cyclohexane with its strategic functional groups all in axial positions leads back to Kemp's triacid 6 , either via the 1,3,5‐trimethyl‐1,3,5‐tris(hydroxymethyl)cyclohexane ( 5b ) or through some other intermediate 6. The methyl substituents could eventually favor cage cyclization, although the hydroxymethyl groups in 5b were shown to be equatorial in the solid state (X‐ray crystallographic structural studies) 7. Alternatively, the bicyclic functionalized ether precursor 7a with two axial “substituents” demands only one final cage formation step, but it has to be synthesized from tetrahydropyran‐4‐one ( 9 ) in a rather lengthy and tedious procedure 8.…”
Section: Resultsmentioning
confidence: 99%
“…Mayer and co-workers indicated that triester 4 (X = trifluoromethylsulfonyloxy) is easily obtained by the reaction of triol 3 with trifluoromethanesulfonic anhydride and is available for the trisubstituted tripodal ligand. 7 In this case, however, the corresponding triamines could not be obtained. We have already shown that the steric repulsion of the ipso methyl groups in the cyclohexane ring causes the unexpected reactions 8 and stabilizes the molecular structures.…”
Section: Resultsmentioning
confidence: 81%
“…As shown in Scheme 1, the esterification of cis,cis-1,3,5-tris(hydroxymethyl)-1,3,5-trimethylcyclohexane (3) 6 with trifluoromethanesulfonic anhydride (4 equiv), 7 followed by reactions with primary amines (4 equiv), gave 3,5,7-trimethyl-1-azonia-adamantanes 2 [2a, R = 2-(pyridin-2-yl)ethyl, 23%; 2b, R = 4-methoxybenzyl, 31%]. The 1 H NMR, 13 C NMR (DEPT), 1 H-13 C COSY spectra supported the structure of 2.…”
Section: Resultsmentioning
confidence: 99%